Above Ground Storage Tanks - Myers, Philip (McGraw-Hill's AccessEngineering., 1997)
The one reference devoted exclusively to ASTs, this book assembles the most critical information on the subject in a single convenient volume. The result is an ideal tool for chemical, environmental, and civil engineers, as well as management and government personnel and others concerned with the regulatory issues governing ASTs. Section by section, this complete reference thoroughly examines and clarifies various types of storage media and their applications; fundamental environmental engineering concerns; industrial codes and standards for ASTs; AST design considerations; the proper construction, fabrication, and erection of tanks; and the often-confusing requirements designed to keep ASTs environmentally sound.